A Systematic Review of the Family Acceptance of a Schizophrenic Patient - Darni, Darni; Yusuf, Ah (International Journal of Psychosocial Rehabilitation, 2020)
Family acceptance provides psychological and behavioral support for patients with schizophrenia shown through a caring attitude and support as a family. This encourages the family members to provide the proper care for the schizophrenic patients. This research was conducted to analyze how families grow in their acceptance of the schizophrenic patients. The research data was the literature used in this systematic review obtained from 3 electronic databases, namely Scopus, Science Direct and Proquest. The articles were published between 2014 and 2019. The literature search and paper selection was based on select keywords. We obtained 42 articles from Scopus, 53 from Science Direct and 38 BMC articles (from the health services). Following this, 56 articles were found to be the same and 48 potential articles were based on the inclusion criteria, namely that they were scientific articles published between 2014-2019 on the Scopus, Google Scholar, Science Direct, and Proquest databases that matched the predetermined criteria. A systematic review was carried out to analyze the articles (PRISMA). A family intervention in the form of acceptance was found to support the decrease in the number of patients with schizophrenia. The results of this research confirm that the acceptance of the family has a positive effect on the family members who experience mental disorders. The positive attitude in which the family support the patient reduces the patients’ vulnerability to negative stigma and discrimination, increasing their tendency to access proper health facilities and overall improving the family acceptance of the family members with a mental disorder. The results of the 15 journals that have been determined based on the inclusion criteria shows that families with a family member with a mental disorder can accept said family member. Future researchers are expected to make this systematic review study a reference to look into increasing the level of acceptance of familial schizophrenia